The effects of structural factors in origin countries on migration: the case of Central and Eastern Europe - Kureková, L (International Migration Institute, 2011)
This paper investigates the relationship between structural change, labour market imbalances and labour migration from the eight Central and Eastern European (CEE/EU8) economies during the transition and after their accession to the EU. The new accession states experienced markedly different migration patterns after 2004 enlargement which, given their similar wage differentials with the West, cannot be explained by the neoclassical framework. The paper deals with this puzzle by developing conceptual and empirical links between different transitional paths of CEE countries and varied migration rates. It argues that structural change that characterized their transition created different labour market imbalances across the CEE economies, hence creating different structures of employment and unemployment and varied risks and opportunities for workers of different demographic and skill profiles. These imbalances and labour market mismatches have in turn induced some workers to seek migration as an exit option more than others, and led to differences in migration rates and in the composition of migrants. In terms of theory, this paper contributes to literature which call for integrated approaches to researching migration that take into account social transformation, pointing out the limited ability of the neoclassical framework to understand migration patterns in their complexity. This paper investigates the relationship between structural change, labour market imbalances and labour migration from the eight Central and Eastern European (CEE/EU8) economies during the transition and after their accession to the EU. The new accession states experienced markedly different migration patterns after 2004 enlargement which, given their similar wage differentials with the West, cannot be explained by the neoclassical framework. The paper deals with this puzzle by developing conceptual and empirical links between different transitional paths of CEE countries and varied migration rates. It argues that structural change that characterized their transition created different labour market imbalances across the CEE economies, hence creating different structures of employment and unemployment and varied risks and opportunities for workers of different demographic and skill profiles. These imbalances and labour market mismatches have in turn induced some workers to seek migration as an exit option more than others, and led to differences in migration rates and in the composition of migrants. In terms of theory, this paper contributes to literature which call for integrated approaches to researching migration that take into account social transformation, pointing out the limited ability of the neoclassical framework to understand migration patterns in their complexity.